Legal Regulation of Children's Sports: The Experience of Ukraine, Norway, Japan, Estonia, and the Republic of Azerbaijan - Ponomarov, Andrii (Problems of legality, 2025)
The article is devoted to the analysis of the legal regulation of children's sports in Ukraine, Norway, Japan, Estonia, and the Republic of Azerbaijan. The study examines legal acts that define the legal status of children in sports, principles of regulation, and the specifics of state policy in this field. The research employs methods of comparative legal analysis, a functional-structural approach, and legal norm analysis. It is revealed that Ukraine's regulatory framework has a technocratic character and requires further development, including the formation of a unified national sports doctrine that would contribute to the creation of an effective system of legal regulation in the sphere of children's sports. A comparative analysis of administrative and legal regulation in Norway and Japan reveals significant differences in their approaches: Norway focuses on mass participation and the development of children’s sports through enjoyment, while Japan emphasizes competitive results and the training of high-performance athletes. The analysis of Estonian and Azerbaijani legislation allows the identification of developmental trends in children's sports in post-Soviet countries. A strategic approach has been developed for further research into the administrative and legal regulation of children's sports in Ukraine and the application of international experience.